A Meta-Analysis of the Effect of Bacillus Calmette-Guérin Vaccination Against Bovine Tuberculosis: Is Perfect the Enemy of Good? - Srinivasan, Sreenidhi; Conlan, Andrew J. K.; Easterling, Laurel A.; Herrera, Christian; Dandapat, Premanshu; Veerasami, Maroudam; Ameni, Gobena; Jindal, Naresh; Raj, Gopal Dhinakar; Wood, James; Juleff, Nick; Bakker, Douwe; et al. (Frontiers in Veterinary Science, 2021)
More than 50 million cattle are likely exposed to bovine tuberculosis (bTB) worldwide, highlighting an urgent need for bTB control strategies in low- and middle-income countries and other regions where the disease remains endemic and test-and-slaughter approaches are unfeasible. While Bacillus Calmette-Guérin (BCG) was first developed as a vaccine for use in cattle even before its widespread use in humans, its efficacy against bTB remains poorly understood. To address this important knowledge gap, we conducted a systematic review and meta-analysis to determine the direct efficacy of BCG against bTB challenge in cattle, and performed scenario analyses with transmission dynamic models incorporating direct and indirect vaccinal effects (“herd-immunity”) to assess potential impact on herd level disease control. The analysis shows a relative risk of infection of 0.75 (95% CI: 0.69, 0.82) in 1858 vaccinates as compared with 1624 controls, corresponding to a direct vaccine efficacy of 25% (95% CI: 18, 31). Importantly, scenario analyses considering both direct and indirect effects suggest that disease prevalence could be driven down close to Officially TB-Free (OTF) status (< 0.1%), if BCG were introduced in the next 10-year time period in low to moderate (<15%) prevalence settings, and that 50-95% of cumulative cases may be averted over the next 50 years even in high (20-40%) disease burden settings with immediate implementation of BCG vaccination. Taken together, the analyses suggest that BCG vaccination may help accelerate control of bTB in endemic settings, particularly with early implementation in the face of dairy intensification in regions that currently lack effective bTB control programs.